1994
DOI: 10.1183/09031936.94.07112038
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental basis for the development of a dynamic airway stent

Abstract: Three major problems are currently associated with airway stents: mucostasis, formation of granulation tissue, and migration. We wanted to determine whether these problems could be solved by a different stent design. Based on theoretical considerations of an idealized trachea, we developed a dynamic bifurcation stent made of silicone which incorporates horseshoe-shaped steel struts. A flexible posterior membrane enables dynamic compression during cough, whilst the clasps maintain the airway lumen in the face o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(6 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The angle of the carina in the airway is not static, and it changes 10° or more with breathing movements and different postures in a normal person (14). In particular, for patients with malignant tumors involving the airway, a 20°-30° change in the angle of the carina should be considered due to the compression on the airway caused by the malignancy (13). In addition, for such patients, stent migration may occur due to tumor shrinkage after tumorspecific therapy (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The angle of the carina in the airway is not static, and it changes 10° or more with breathing movements and different postures in a normal person (14). In particular, for patients with malignant tumors involving the airway, a 20°-30° change in the angle of the carina should be considered due to the compression on the airway caused by the malignancy (13). In addition, for such patients, stent migration may occur due to tumor shrinkage after tumorspecific therapy (34).…”
Section: Discussionmentioning
confidence: 99%
“…However, no studies have focused on the treatment of malignant stenosis around the carina or bronchi with metallic stents customized by 3D printing. It should be noted that the angle between the two main bronchi may vary in patients with tumor compression or during respiration (13,14). Therefore, we designed a new segmented airway stent with a changeable angle between these two branches to fit the dynamic changes of the carina angle.…”
Section: Introductionmentioning
confidence: 99%
“…28 Freitag developed the Dynamic Y stent (Boston Scientific Corporation, Natick, MA), which was composed of silicone embedded with anterolateral horseshoe-shaped steel struts, attempting to mimic the anatomical properties of the trachea. 29,30 Deployment was complex and performed via laryngoscope or rigid bronchoscope with specially designed introducer forceps. 31 The stent demonstrated considerable promise when first created 32 ; however, it has been discontinued globally, most likely due to difficulty with insertion.…”
Section: Metallic Stentsmentioning
confidence: 99%
“…The results showed that the airway deformation caused by tracheal movement significantly affects the stent's mechanical properties. Freitag et al [ 14 ] conducted dynamic and static load simulation on isolated human trachea with a stent to study the stent's stability in trachea deformation. In the field of studying the nonlinearity and shedding mechanism of Ni–Ti alloy stents, Guo et al [ 15 ] established the nonlinear dynamic response of shape memory alloy tracheal stents by considering the influence of random excitation, such as random radial pressure.…”
Section: Introductionmentioning
confidence: 99%